English furniture - Rogers, John C. ([place of publication not identified] : Spring Books, 1967)
This book was published in 1923 after Macquiod's History of English Furniture. In English Furniture, John Rogers approached furniture from a different construction; and the precise and workmanlike analyses of types of furniture were accompanied by diagrams which are of value to the students and the ever-widening circle of those interested in the art of the English craftsman.
The period of oak furniture -- The period of walnut furniture -- The period of mahogany furniture.
Includes index.
Keywords: FURNITURE -- ENGLAND -- HISTORY